(untitled) (Research, Society and Development, 2019)
Several everyday materials have acid-base indicator properties. This article aims to develop a reference material on acid-base indicators made from these materials, which can be used by the professor of Chemistry in the content of Acids and Bases to carry out the identification of these, and in this way, to be able to contextualize their teaching with the daily life of the students, who often associate the contents of Chemistry with something difficult to understand and without applications in everyday life. A total of 10 substances (purple grape, açaí, black olives, purple cabbage, black beans, jasmine-mango flower, minilacre flower, hibiscus flower, purple onion and eggplant) were selected for the preparation of the extracts, which were made using ethyl alcohol, found in pharmacies and markets, for a period of 24 hours. The extracts were tested on four substances: commercial muriatic acid, commercial caustic soda, vinegar and soap. All the indicators present satisfactory results, being able to identify with acid and basic substances distinction, which allows to infer that they can be used as a teaching tool by the professor of Chemistry.